Implications of institutional racism in the therapeutic itinerary of people with chronic renal failure - Santos Ferreira, Ricardo Bruno; de Camargo, Climene Laura; da Silva Barbosa, Maria Inês; Silva Servo, Maria Lúcia; Carneiro Oliveira, Marcia Maria; Alves Leite Leal, Juliana (Investigación y Educación en Enfermería, 2020)
Objective. To understand the implications of institutional racism in the therapeutic itinerary of patients with chronic renal failure (CRF) in the search for diagnosis and treatment of the disease. Methods. Descriptive, qualitative study developed with 23 people with CRF in a regional reference hospital for hemodialysis treatment in Northeast Brazil. Two techniques of data collection were used: semi-structured interview and consultation to the NEFRODATA electronic medical record. For systematization and analysis, the technique of content analysis was used. Results. Black and white people with CRF showed significant divergences and differences in their therapeutic itineraries: while white people had access to diagnosis during outpatient care in other medical specialties, black people were only diagnosed during hospitalization. In addition, white people had more access to private health plans when compared to black people, which doubles the possibility of access to health services. Moreover, even when the characteristics in the itinerary of black and white people were convergent, access to diagnosis and treatment proved to be more difficult for black people. Conclusion. The study showed the presence of institutional racism in the therapeutic itinerary of people with kidney disease in which black people have greater difficulty in accessing health services. In this sense, there is a need to create strategies to face institutional racism and to consolidate the National Policy for Comprehensive Health Care of the Black Population.